2021
DOI: 10.3389/fneur.2021.755167
|View full text |Cite
|
Sign up to set email alerts
|

Transient Ischemic Attacks Preceding Ischemic Stroke and the Possible Preconditioning of the Human Brain: A Systematic Review and Meta-Analysis

Abstract: Stroke is a leading cause of mortality and disability worldwide. Transient ischemic attack (TIA) is defined as transient brain ischemia with temporary neurological deficits. In animal models, prior TIA seems to enhance brain ischemic tolerance to withstand further ischemic events, which might be explained by brain preconditioning. Thus, this review aims to formulate evidence of whether TIAs can induce positive preconditioning and enhance the functional outcomes in patients suffering from subsequent ischemic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…TIA is a common ischemic cerebrovascular disease, consistent with endogenous local ischemic preconditioning. Evidence has shown that stroke patients with prior TIA have a better prognosis than those without TIA, indicating that TIA induces ischemic tolerance [ 26 , [36] , [37] , [38] , [39] ]. It was supported by a systematic review and meta-analysis, revealing that patients with prior TIA had lower NIHSS scores at admission and lower scores on discharge [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…TIA is a common ischemic cerebrovascular disease, consistent with endogenous local ischemic preconditioning. Evidence has shown that stroke patients with prior TIA have a better prognosis than those without TIA, indicating that TIA induces ischemic tolerance [ 26 , [36] , [37] , [38] , [39] ]. It was supported by a systematic review and meta-analysis, revealing that patients with prior TIA had lower NIHSS scores at admission and lower scores on discharge [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Innovatively, we predicted the occurrence of AIS within three years in a patient cohort defined by three stratifying factors: elderly age, transient ischemic attack (TIA), and hypertension. Each of these is a key factor for AIS incidence 4 , 9 , 44 , and older hypertensive patients with TIA are undoubtedly a high-risk group in need of predictive assessment for AIS. We opted for the simplest model comprising only seven PDHIs ('SIRI', 'HCT', 'RDW_CV', 'PLT', 'BAS_p', 'IG_p', and 'EOS'), given its comparable performance to more complex models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the presence of a prior TIA was associated with a favorable outcome in ischemic stroke patients, suggesting a neuroprotective effect of TIA possibly by inducing a phenomenon of ischemic tolerance allowing better recovery from a subsequent ischemic stroke [ 28 , 29 ]. However, some studies failed to confirm this [ 30 ]. The discrepancy of results may result from the difference in the type of stroke, inconsistent definition of study endpoint, and bias in the record of previous TIA.…”
Section: Discussionmentioning
confidence: 99%